2012
DOI: 10.1016/j.biopsych.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention May Prevent the Development of Posttraumatic Stress Disorder: A Randomized Pilot Civilian Study with Modified Prolonged Exposure

Abstract: Background Posttraumatic stress disorder is a major public health concern with long term sequelae. There are no accepted interventions delivered in the immediate aftermath of trauma. This study tested an early intervention aimed at modifying the memory to prevent the development of PTSD prior to memory consolidation. Methods Patients (N=137) were randomly assigned to receive 3 sessions of an early intervention beginning in the emergency department (ED) compared to an assessment only control group. Posttrauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
237
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 51 publications
(55 reference statements)
3
237
3
6
Order By: Relevance
“…Although evidence-based interventions for PTSD are available (Bisson et al, 2007), studies examining interventions to prevent PTSD’s onset have not been encouraging, and the majority of these studies have shown that they are ineffective or may even increase PTSD symptoms (e.g. psychological debriefing; Rose, Bisson, Churchill, & Wessely, 2002; Sijbrandij, Olff, Reitsma, Carlier, & Gersons, 2006; but see Rothbaum et al, 2012). Currently, interventions that can be offered to trauma survivors in the immediate aftermath are lacking and there is a high unmet need for effective early interventions that can relieve initial trauma symptoms and reduce PTSD rates (Kearns, Ressler, Zatzick, & Rothbaum, 2012; Qi, Gevonden, & Shalev, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence-based interventions for PTSD are available (Bisson et al, 2007), studies examining interventions to prevent PTSD’s onset have not been encouraging, and the majority of these studies have shown that they are ineffective or may even increase PTSD symptoms (e.g. psychological debriefing; Rose, Bisson, Churchill, & Wessely, 2002; Sijbrandij, Olff, Reitsma, Carlier, & Gersons, 2006; but see Rothbaum et al, 2012). Currently, interventions that can be offered to trauma survivors in the immediate aftermath are lacking and there is a high unmet need for effective early interventions that can relieve initial trauma symptoms and reduce PTSD rates (Kearns, Ressler, Zatzick, & Rothbaum, 2012; Qi, Gevonden, & Shalev, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is one of the few psychiatric disorders with a clear onset event (the trauma), and thus prevention strategies would be relatively applicable. However, to date effective preventive interventions are lacking, although some studies have found trauma focused Cognitive Behavioural Therapy (CBT) to be effective (Roberts, Kitchiner, Kenardy, & Bisson, 2010; Rothbaum et al, 2012; Sijbrandij et al, 2007). …”
mentioning
confidence: 99%
“…Results were divided according to the type of intervention (pharmacological or psychological). From the 29 articles reviewed, 16 reported significant effects of interventions for the prevention of PTSD or symptoms related to the disorder [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Of these, 22 studies used psychological interventions and 7 used pharmacological interventions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Four of the six studies that used CBT or related techniques reported results compatible with reduced occurrence of PTSD or PTSDrelated symptoms in groups who underwent interventions in relation to control groups 9,[17][18][19] . In the study by Mouthaan et al 24 , which did not report reductions in the occurrence of PTSD, the authors discuss the fact that one-fifth of the volunteers failed to adhere to the intervention program.…”
Section: Cognitive Behavioral Therapy (Cbt)mentioning
confidence: 98%
See 1 more Smart Citation